AN ANALYSIS OF TRANSLATION METHOD FROM INDONESIA TO ENGLISH IN INDONESIA SONGS “ CINTANYA AKU” COVERED BY EMMA HEETERS - Iman Kristiani Gulo; Agnes Foneria Zebua; Tantri Aurelia Gulo; Anatasya Novanda Aritonang (Merwin Publisher, 2025)
This research examines the translation techniques employed in the English version of the Indonesian song